Interpreting films : studies in the historical reception of American cinema - Staiger, Janet (Princeton University Press, 1992)
Employing a wide range of examples from Uncle Tom's Cabin and Birth of a Nation to Zelig and Personal Best, Janet Staiger argues that a historical examination of spectators' responses to films can make a valuable contribution to the history, criticism, and philosophy of cultural products. She maintains that as artifacts, films do not contain immanent meanings, that differences among interpretations have historical bases, and that these variations are due to social.
Keywords: Motion pictures -- Aesthetics.; Reader-response criticism.; Motion pictures -- United States.; Cinéma -- Esthétique.; Esthétique de la réception.; Cinéma -- États-Unis.; PERFORMING ARTS -- Film & Video -- History & Criticism.; Motion pictures; Motion pictures -- Aesthetics; Reader-response criticism; United States; Films.; Receptie.; Cinema -- Films (Motion pictures) -- History